A numerical model for simulation of RC beam-column connections. (1st April 2015) - Omidi, Morteza; Behnamfar, Farhad
Highlights: A numerical model for simulation of RC beam-column connections is presented. Model consists of a rigid offset, beam and column elements with concentrated plasticity. The model follows the seismic response of connections with a very good accuracy. Abstract: Beam to column connections in reinforced concrete (RC) frames are among the elements having essential effects in determining the performance and behavior of structure under different loads. Role of these connections against the lateral loads especially strong earthquakes is such important that experience of past earthquakes confirm their effect in defining value and extent of structural damages. Therefore, to appropriately address the seismic performance of new or existing RC frames, engineers need models able to predict the connection behavior with an acceptable accuracy and enough simplicity. In this research, a numerical model for simulating the elastic and inelastic behavior of RC beam-column connections is presented. This model consists of a rigid offset element and beam and column elements with concentrated plasticity. The rigid offset element is calibrated to give a good estimation of the initial stiffness based on the shear demand ratio of the connection. Each of the beam and column elements with concentrated plasticity includes two rotational springs in series. One spring represents the nonlinear behavior of beam and column and the other contains the nonlinear behavior of the connection. Each one of the rotational springs possesses its own moment-rotation response curve. Comparison of the simulated response with that of the existing experimental results confirms that the suggested model follows the seismic response of beam-column connections with a very good accuracy.